2017
DOI: 10.1007/s10856-017-5999-z
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin-Pellethane® cardiovascular patches: Effect of silk fibroin concentration on vascular remodeling in rat model

Abstract: Life-threatening cardiovascular anomalies require surgery for structural repair with cardiovascular patches. The biomaterial patch, derived from Bombyx mori silk fibroin (SF), is used as an alternative material due to its excellent tissue affinity and biocompatibility. However, SF lacks the elastomeric characteristics required for a cardiovascular patch. In order to overcome this shortcoming, we combined the thermoplastic polyurethane, Pellethane® (PU) with SF to develop an elastic biocompatible patch. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Silk fibroin (SF), a kind of natural protein derived from silkworm cocoons, is a widely used as one of the most popular materials for biomedical applications due to its distinct biological properties [ 1 , 2 ], such as good biocompatibility, biodegradability, good cell adhesion and non-toxicity [ 3 , 4 ]. In recent years, many researches have shown that SF biomaterials can be applied widely in tissue engineering scaffolds [ 5 , 6 ], blood vessel tissue engineering [ 7 ], bone tissue engineering [ 8 ], drug delivery systems, and so on [ 9 , 10 , 11 , 12 ]. Through being dissolved and purified, SF obtained from degummed silk can be used to prepare a variety of biomaterials, such as membranes, gels and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF), a kind of natural protein derived from silkworm cocoons, is a widely used as one of the most popular materials for biomedical applications due to its distinct biological properties [ 1 , 2 ], such as good biocompatibility, biodegradability, good cell adhesion and non-toxicity [ 3 , 4 ]. In recent years, many researches have shown that SF biomaterials can be applied widely in tissue engineering scaffolds [ 5 , 6 ], blood vessel tissue engineering [ 7 ], bone tissue engineering [ 8 ], drug delivery systems, and so on [ 9 , 10 , 11 , 12 ]. Through being dissolved and purified, SF obtained from degummed silk can be used to prepare a variety of biomaterials, such as membranes, gels and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…SF was also incorporated into cardiovascular patches purposed for vascular surgery [41,45]. Additionally, an in vivo study confirmed SF to have favorable biological and physical properties, and that it can be effectively used in vessel reconstruction surgery [41].…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, studies that employed SF as an artificial vessel confirmed it to have excellent hemocompatibility, cell viability, tissue integrity, and mechanical strength [42][43][44]. SF was also incorporated into cardiovascular patches purposed for vascular surgery [41,45]. Additionally, an in vivo study confirmed SF to have favorable biological and physical properties, and that it can be effectively used in vessel reconstruction surgery [41].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations